Kinetics and Mechanism of Hydrolysis of Di-p-sulphonic Acid Aniline Phosphate in Acidic Medium - Shinde, C.P.; Patil, R.; Shirdhonkar, Vaishali (Asian Journal of Chemistry, 2010)
Investigation of di-p-sulphonic acid aniline phosphate was carried outby using "Allen's" modified method of colorimetry in acid medium from0.1 to 7.0 mol dm-3 at 98°C in 20% dioxane-water mixture (V/V). Ionicstrength data exhibit different contribution of neutral species and presenceof acid catalysis. Theoretical rates estimated from 2nd empirical term ofDebye-Htickel equation have been found in close agreement with experimentalrates. Ionic strength, temperature, solvent of kinetic studies areprovided to identify the reactive species. Molecularity and bond fissionare also discussed in terms of Zucker-Hammett hypothesis, Hammett acidityfunctions, Btinnett and Btinnett-Olsen parameters and isokinetic relationship.